THE EQUALITY OF AQUATIC ANIMAL BEHAVIOR METAPHORS AND HUMAN BEHAVIOR METAPHORS: A COGNITIVE SEMANTIC ANALYSIS: KESAMAAN METAFORA PERILAKU HEWAN DAN METAFORA PERILAKU MANUSIA: KAJIAN SEMANTIK KOGNITIF - Fadhila Afiya; Elvi Citraresmana; Hera Meganova Lyra (Jurnal Kata, 2023)
This study intends to analyze the equality of aquatic animal metaphors and human behavior found in sekiman ‘Lampung proverbs’ as well as to relate it to the mindset of the people associated with the sekiman. The method used in this research is the descriptive qualitative. Then, the data on sekiman ‘Lampung proverbs’ containing aquatic animals were obtained from Sasikun Kicik Lampung: Pribahasa Orang Lampung (1996) book. After that, data triangulation was done through interviews. The data collected focused on proverbs that contain elements of aquatic animals and amphibians. Based on the analysis, researchers found structural metaphors with conceptual meanings of wandering, ability, gossip, thoroughness, service, help, imposing will, stupidity, disrespect, vanity, gluttony, carelessness, and stubbornness. Through those conceptual meanings, researchers reveal identity image schemes of bad manners, identity image scheme to the contribution, and identity image scheme to uselessness. Furthermore, the researchers identify the image schemes scale subtheme of path, ability, prudence, and force. Finally, positive cognitive image metaphors and negative cognitive image metaphors are also identified.